2019
DOI: 10.1016/j.lcsi.2019.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge co-construction activities and task-related monitoring in scripted collaborative learning

Abstract: This study explores teacher education students' knowledge co-construction activities, taskrelated monitoring and script use in collaborative learning situations. The specific aims are to investigate how students engage in knowledge co-construction activities and to compare taskrelated monitoring and script use in groups with active and passive knowledge coconstruction. The participants of this study were five small groups of teacher education students (N = 19); collaborative learning in these groups was suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 68 publications
2
24
0
2
Order By: Relevance
“…The study showed that children were able to work with the four steps on the worksheet that guided them through the cooperative knowledge-sharing process. In addition, in line with the literature (e.g., Vuopala et al 2019), an initial comparison with groups that did not use the worksheet showed that there was a more equal distribution of contributions to the cooperative process in the worksheet groups. However, the second step of the worksheet, which focused on writing down knowledge that was shared by the other group members, was not self-evident.…”
Section: Designing the Heterogeneous Design Phasesupporting
confidence: 68%
“…The study showed that children were able to work with the four steps on the worksheet that guided them through the cooperative knowledge-sharing process. In addition, in line with the literature (e.g., Vuopala et al 2019), an initial comparison with groups that did not use the worksheet showed that there was a more equal distribution of contributions to the cooperative process in the worksheet groups. However, the second step of the worksheet, which focused on writing down knowledge that was shared by the other group members, was not self-evident.…”
Section: Designing the Heterogeneous Design Phasesupporting
confidence: 68%
“…We ground this study in the increasing empirical understanding of the multifaceted interaction processes involved in collaborative learning, integrating cognitive, and affective components as the core of collaboration (Volet et al, 2009;Järvel et al, 2010Järvel et al, , 2013Näykki et al, 2014;Ucan and Webb, 2015;Sobocinski et al, 2016;Isohätälä et al, 2019a;Vuopala et al, 2019). In theory, collaborative learning requires group members to be aware of and to coordinate with their cognitive, metacognitive, motivational, and emotional resources and efforts (Hadwin et al, 2018).…”
Section: Collaborative Learning As a Cognitive And Affective Learningmentioning
confidence: 99%
“…Active participation in knowledge-sharing activities is known to lead to higher learning outcomes (Vuopala et al, 2019). To reach active participation, it is important that domain-related knowledge is shared within the group (Webb, 1982a(Webb, , 1982b(Webb, , 1984, that this knowledge is elaborated upon (van den Bossche, Gijselaers, Segers, & Kirschner, 2006;Webb, 1991), and that group members equally participate in the dialogue (Weinberger & Fischer, 2006).…”
Section: Hypothesesmentioning
confidence: 99%